Poly(lactic acid)-based polymer composites with high electric and thermal conductivity and their characterization - Lebedev S. M. Sergey Mikhailovich; Gefle O. S. Olga Semenovna; Amitov E. T. Ernar Tanirbergenuly; Berchuk D. Yu. Denis Yurievich; Zhuravlev D. V. Denis Vladimirovich (2016, 2016)
Title screen